Remnant surfaces in the Tárkány Basin - Pecsmány, Péter; Hegedűs, András; Vágó, János (Acta Geographica Debrecina Landscape & Environment series, 2020)
The terraces of the Tárkány Basin, located in the SW part of the Bükk Mountains are known since the beginning of the 20th century. Based on field surveys, six morphological levels were delineated and described in 1936. During the later geological mapping surveys, three gravel terraces had been mapped in the basin. Since then, no comprehensive morphological mapping has been made in the Tárkány Basin. Our study aimed to validate the results of these early studies using a digital elevation model. We delineated the remnant surfaces of the basin by morphometric and GIS techniques. Then, based on field surveys and former geological maps; we characterised these remnant surfaces, and their area was measured as well. The results of this study contribute to a better understanding of the surface evolution of the basin and its surroundings.